What Causes the Discrepancy in SARS-CoV-2 Vaccine Between Parental Hesitancy for Themselves and for Their Children During Lockdown Period? - Tianshuo Zhao; Chao Wang; Sihui Zhang; Linyi Chen; Bingfeng Han; Hanyu Liu; Mingzhu Xie; Xianming Cai; Shanshan Zhang; Yiguo Zhou; Guoxing Li; Bei Liu; et al. (Springer, 2023)
Abstract Background Parents are usually the decision-makers for vaccinations of children. Therefore, it is important to understand parental beliefs and attitudes toward severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine for themselves and their children when it was approved for children age 3-17. Method A cross-sectional survey based on an anonymous online questionnaire for parents was conducted in seven provinces of China, and demographic information, vaccination history, parental decision motives, and health belief model toward themselves and their children were collected, respectively. Results The overall parental hesitancy rate toward themselves was 20.30%, and that toward their children was 7.80%. More parental concerns on disease severity (odd ratio [OR] = 1.11, 95% confidence interval [CI]: 1.01-1.61) and susceptibility (OR = 1.29, 95% CI: 1.01-1.63) of children could be the causes of discrepancy in hesitancy for themselves and for their children. Parents who hesitated to vaccinate themselves might also be hesitated to vaccinate their children (β = 0.077, P < 0.001). Conclusion Threat perception may lead to inconsistencies in parental vaccination decisions toward themselves and toward their children. Correcting misinformation and strengthening education about COVID-19 are of great significance in addressing vaccine hesitancy among parents and children.